CREATIVE ENTREPRENEURSHIP WORKSHOP DEVELOPING INNOVATIVE BUSINESS IDEAS AMONG STUDENTS OF MA AL-ULYA AL MUBAROK - Maulana, Maulana; Susanto, Denies; Permadi, Bambang (Yayasan Education and Social Center, 2025)
The purpose of this study is to understand how to develop an innovative creative approach to enhancing entrepreneurial spirit and to assess the effectiveness of this approach in improving entrepreneurial spirit. The background of this study is based on the fact that entrepreneurship education implemented so far has only emphasized the cognitive aspect. In addition, the low interest of students in participating in the Creative Entrepreneurship Workshop on Developing Innovative Business Ideas among Students also indicates that students' entrepreneurial spirit is lacking. This study uses the Research and Development (R&D) method with the Four D model, which includes define, design, develop, and disseminate. Data collection in this study was conducted using a questionnaire. The data analysis techniques employed were qualitative descriptive analysis and inferential statistical analysis using the independent sample t-test. The results of this study are: 1) The development of an innovative creative approach to improving entrepreneurial spirit is carried out using the four Ds: define, design, develop, and disseminate; 2) The innovative creative approach is very effective in improving entrepreneurial spirit. Entrepreneurship plays a significant role in driving a country's economy. Entrepreneurs not only create jobs for the community but also enhance productivity through innovation. They are the main drivers of economic transformation, bringing new ideas to the market and creating added value. In this context, the younger generation, especially students, stands out as a great potential source for developing entrepreneurship. They tend to have high enthusiasm, abundant creativity, and strong innovative capabilities, which are vital assets in the business world.